MONITORING AND EVALUATION OF THE DEGREE OF CONTAMINATION IN CHEMISTRY AND CHEMISTRY ENGINEERING LABORATORIES (FQIQ) AND ITS IMPACT ON HEALTH AND THE ENVIRONMENT - Sandívar, Juana (2014)
We evaluated the hypothesis that an exposure of at least 20 hours per week with reagents during academic practice or research projects of teachers, workers and students of Chemistry and Chemistry Engineering Faculty of San Marcos University, caused an increase in biomarkers of exposure of early effect. The frequency of micronuclei in the oral mucosa was analyzed to check the cytogenetic effect in two populations: Problem Group and Control Group. In each population was taken three groups totaling 85 individuals: teachers (mean age: 56,6 ± 6,48), non-teaching staff (mean age: 48,5 ± 17,5) and students (mean age 25,14 ± 4,99). We used the micronucleus test (Mn) in epithelial cells of the oral mucosa. When comparing the values obtained from DNA damage for each individual and for statistical analysis, ANOVA was applied with a significance value of 95% reliability. Damage was found at the cellular level of the population problem, mainly at nucleus (nuclear aberrations). The most common injury was binucleated cell (26,70 ± 16,44), followed by cells with karyolysis (7,17 ± 5,89), pyknosis (3,70 ± 2,46) and "broken egg" (3,17 ± 3,92). No relationship was found with respect to age groups evaluated. As for the relationship between the types of the workers, non-teaching employees have greater damage (47.00 ± 16.46), followed by teachers (29,50 ± 14,50) and students (17,00 ± 10,00). In conclusion, there is cytotoxic, genotoxic and apoptotic damage in the population issue, probably by chronic exposure to chemicals that damage cellular DNA integrity.